2019
DOI: 10.1016/j.chempr.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Photoredox-Catalysis-Modulated, Nickel-Catalyzed Divergent Difunctionalization of Ethylene

Abstract: Functionalization of ethylene without polymerization is challenging under photoirradiation conditions. We have demonstrated that the photo-transformation of ethylene can be controllable by merging photoredox and transition-metal catalysis. In our study, the use of different photoredox catalysts was able to modulate the oxidation state of the nickel catalyst. Through different oxidation states, the nickel-catalyzed couplings proceeded via distinct pathways to generate divergent ethylene difunctionalization prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(59 citation statements)
references
References 39 publications
1
57
0
1
Order By: Relevance
“…Having established the powerful and selective synthetic method for the generation of sulfones and sulfoxides and the modification of pharmaceuticals, we explored the intrinsic mechanism. First, labeling experiments with H 2 18 O and 18 O 2 unambiguously confirmed that the oxygen atoms on the sulfoxides and sulfones originated from the oxygen atmosphere and not from water (Section SVI‐1).…”
Section: Discussionmentioning
confidence: 99%
“…Having established the powerful and selective synthetic method for the generation of sulfones and sulfoxides and the modification of pharmaceuticals, we explored the intrinsic mechanism. First, labeling experiments with H 2 18 O and 18 O 2 unambiguously confirmed that the oxygen atoms on the sulfoxides and sulfones originated from the oxygen atmosphere and not from water (Section SVI‐1).…”
Section: Discussionmentioning
confidence: 99%
“…Having established the powerful and selective synthetic method [29] for the generation of sulfones and sulfoxides and the modification of pharmaceuticals,weexplored the intrinsic mechanism. First, labeling experiments with H 2 18 Oa nd 18 O 2 unambiguously confirmed that the oxygen atoms on the sulfoxides and sulfones originated from the oxygen atmosphere and not from water (Section SVI-1).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Wu and coworkers reported a photoredox/nickel catalyzed difunctionalization of ethylene with aryl halides in the presence of a stoichiometric amount of organic reductants, affording 1,2-diarylethanes with good efficiency (Scheme 19). 29 In this process, the oxidative addition of an active catalyst Ni I with an aryl halide would give an aryl-Ni III species, which undergoes migratory insertion of ethylene to generate a cationic alkyl-Ni III species with the dissociation of a halide ligand. Mechanistic studies and DFT calculations provided support for this proposed pathway.…”
Section: Nonradical Pathway Cascade Reactionmentioning
confidence: 99%